A Newly Identified Complication of Patellofemoral Arthroplasty: Case Report and Literature Review. (31st October 2022) - Solarino, Giuseppe; Maccagnano, Giuseppe; Vicenti, Giovanni; Buono, Claudio; Simone, Filippo; Ottaviani, Guglielmo; Zavattini, Giacomo; Zaccari, Domenico; Carrozzo, Massimiliano; Spinarelli, Antonio; Bizzoca, Davide; Moretti, Biagio
Background: Patellofemoral arthroplasty (PFA) is a surgical option for patients older than 40 years old who are affected by patellofemoral osteoarthritis. Regarding the complications of PFAs, few studies have investigated periprosthetic fractures. The purpose of this literature review was to highlight a previously overlooked complication of primary prosthetic surgery of the patellofemoral joint. Methods: Three literature databases were searched for studies published between 2000 to 2020 using relevant keywords. A total of 4, 942 articles were originally identified. After excluding duplicates and analysing the titles and abstracts, 20 studies were considered. From these, data regarding the number of cases, clinical outcomes and complications were extracted. Results: Among the 20 selected articles, only one described periprosthetic fractures as a complication of PFAs. Herein, we also report an illustrative case of an unknown fracture complication. No cases in the literature were found that described the type of complications experienced by our patient during the postoperative period. Conclusions: This review confirms the lack of data about clinical outcomes and fracture complications of PFAs. In primary prosthetic surgery of the patellofemoral joint, patient selection and close consideration of demographic factors (such as BMI and age) and intraoperative factors (such as patellar thickness and size of the trochlear component) play a key role in optimising pre-operative planning to avoid intraoperative periprosthetic fractures.